2021
DOI: 10.22409/antropolitica2021.i51.a44595
|View full text |Cite
|
Sign up to set email alerts
|

Audiência de Custódia e Violência Policial: Análise do Encaminhamento das Denúncias em Duas Gestões na Cidade de São Paulo

Abstract: Este artigo discute o encaminhamento institucional dado aos relatos de violência policial nas audiências de custódia realizadas na cidade de São Paulo, fazendo uma análise comparativa entre duas gestões na coordenação do projeto. As análises consolidam as trajetórias de pesquisas das autoras que, desde 2015 com a implantação do projeto, até 2020, com sua suspensão em decorrência da pandemia de Covid-19, coletam dados por meio de observação direta e de entrevistas com os operadores envolvidos nas audiências. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…While initially created for safeguarding the rights of people arrested by the police and expedite their presence before a judge, a prosecutor, and a defense attorney, 8 recent researches on custody hearings have revealed that this legal device has deviated from its original intent and sedimented itself within the “old” mechanisms of the criminal justice system (Azevedo et al ., 2018). According to the literature, despite providing for the possibility of investigating police violence, custody hearings have become a standard legal procedure, focused on swiftness and productivity (Silvestre et al, 2020). The expectation that a meeting between a detainee and a judge, a prosecutor, and an attorney could impact decisions and reduce the frequency of preventive arrests did not come to fruition.…”
Section: Custody Hearingsmentioning
confidence: 99%
“…While initially created for safeguarding the rights of people arrested by the police and expedite their presence before a judge, a prosecutor, and a defense attorney, 8 recent researches on custody hearings have revealed that this legal device has deviated from its original intent and sedimented itself within the “old” mechanisms of the criminal justice system (Azevedo et al ., 2018). According to the literature, despite providing for the possibility of investigating police violence, custody hearings have become a standard legal procedure, focused on swiftness and productivity (Silvestre et al, 2020). The expectation that a meeting between a detainee and a judge, a prosecutor, and an attorney could impact decisions and reduce the frequency of preventive arrests did not come to fruition.…”
Section: Custody Hearingsmentioning
confidence: 99%
“…Além disso, outras decisões relacionadas ao funcionamento das audiências também podem estar associadas a gestão do juiz corregedor. Na ocasião da implementação das audiências de custódia a gestão do DIPO foi considerada aberta à pesquisa (Silvestre et al, 2020), o que contribuiu para a realização das pesquisas citadas anteriormente. Em 2018 ocorreu uma mudança na gestão do DIPO e assumiu o departamento uma juíza conhecida pela rigidez de suas decisões.…”
Section: Escolhas Metodológicasunclassified
“…Em 2018 ocorreu uma mudança na gestão do DIPO e assumiu o departamento uma juíza conhecida pela rigidez de suas decisões. Conforme apontam Silvestre et al (2020), essa rigidez se refletiu também no tratamento dado à pesquisa e os pesquisadores.…”
Section: Escolhas Metodológicasunclassified
See 1 more Smart Citation